Assessment of memory functioning over two years following severe childhood traumatic brain injury: results of the TGE cohort. (29th July 2019) - Viot, Solène; Câmara-Costa, Hugo; Laurence, Watier; Francillette, Leila; Toure, Hanna; Brugel, Dominique; Laurent-Vannier, Anne; Dellatolas, Georges; Gillibert, André; Meyer, Philippe; Chevignard, Mathilde
ABSTRACT: The aims of this study were (1) to prospectively measure memory functioning following severe childhood Traumatic Brain Injury (TBI), and its evolution over 2 years; (2) to assess demographic and medical factors associated with memory function and recovery; (3) to explore relations between memory and other TBI outcomes. Methods : Children (aged 0–15 years; n = 65) consecutively admitted in a single trauma center over a 3-year period, who survived severe non-inflicted TBI, were included in a prospective longitudinal study. Memory was assessed in 38 children aged 5–15 years at injury, using the Children's Memory Scale at 3, 12, and 24 months post-injury. Results : Mean general memory score was low at 3 months (M = 90.2, SD = 20.3) but within the normal range at 12 and 24 months (M = 100.6, SD = 23.1 and M = 108.6, SD = 24.1, respectively), with high variability. Improvement was stronger for immediate visual memory than for other memory indices. Lower general memory score was associated with higher injury severity, lower intellectual ability and functional status, higher overall disability, and ongoing education. Conclusion : Memory functioning is highly variable following severe childhood TBI, related to injury severity and functional, cognitive and educational outcomes; improvement is significant during the first-year post-injury, but varies according to the type of memory.